The Impacts of Drawing, Visualization and Rote Memorization on Iranian EFL Students’ English Vocabulary Recall and Retention - امیر حسین سرکشیکیان; سید عبدالمجید طباطبایی لطفی; Saeide Hosseini (Journal of Applied Linguistics, 2024)
Given the role of lexical knowledge in language learning, strategies for vocabulary learning should be paid more attention in the literature. This study investigated the effects of visualization, drawing, and memorization on Iranian EFL learners' recall and retention of second language vocabulary using a quasi-experimental comparison design . To that end, three intact classes, incorporating sixty students in total , were randomly selected as the experimental groups of this study. Nation’s (2006) vocabulary size test was administered to them to homogenize them in terms of English lexical knowledge. The results of one-way ANOVA demonstrated that there were no significant differences among the three groups in terms of vocabulary knowledge. A piloted researcher-made vocabulary test was administered to the participants as the pretest and post-tests. The one-way ANOVA results showed that there were no significant between-group differences among the groups' performances on the immediate and delayed posttests. However, the results of a repeated-measures ANOVA indicated that the three strategies had a significant within-group effect on the three groups' vocabulary recall, while their vocabulary retention was found to have dropped significantly from immediate to the delayed posttest. All the same, the drawing group had the best performance from the pretest to the immediate posttest, and the control group was the weakest on delayed posttest. Finally, the findings are discussed, and implications are offered for EFL teachers and learners.